Performance of an upflow anaerobic biofilter for treatment of POME. - Suki , A.; Idris, Azni; Megat Mohd Noor, Megat Johari
The upflow anaerobic packed bed biofilter was evaluated to determine its effectiveness in treating Palm Oil Mill Effluent (POME). Three reactors with total volumes of 52, 52 and 290 litres and packed with 1/2, 1 and 1 inch rings were evaluated. The results shows a COD removal ranging from 66% to 94% and an SS removal ranging from 77 to 94% depending on the loading rate. Retention times used were 5 and 10 days and high removal rate was still possible at the low retention time. Start up for the reactor is within one month and growth of the biomass probably required more than two months. The removal of nutrient were also assessed.